Improving Sleep Quality and Blood Pressure Through Warm Foot Soak in the Elderly - Mulya, Cahya; Sulistyowati, Dwi; Astuti, Athanasia Budi (Poltekkes Kemenkes Surakarta, 2023)
Background: Hypertension can lead to decreased sleep quality in the elderly. Nursing interventions are needed to overcome sleep disorders in the elderly. This study analyses the effect of warm water foot bath therapy on reducing blood pressure and improving sleep quality in elderly people with hypertension who experience sleep disorders. Methods: Pre-experimental research with one group pre-post test design method. The purposive sampling technique was 37 respondents. Research instrument questionnaire sheet. Friedman statistical test. Results: Friedman test results p value < 0.001. Sleep quality before warm water soaking results in moderate PSQI scores (37.8%) and respondents with poor PSQI scores (62.2%). After the warm water soak, the PSQI score was good (8.1%), respondents with mild PSQI scores (18.9%) and respondents with moderate PSQI scores (73%). Friedman test p value <0.001. Conclusion: Warm water foot baths can reduce blood pressure and improve sleep quality in the elderly. This therapy can be used as a nursing intervention in the elderly who experience hypertension and sleep disorders.